2020
DOI: 10.1590/0001-3765202020190585
|View full text |Cite
|
Sign up to set email alerts
|

Correlation profile of the heavy metal distribution in the Pontastacus leptodactylus tissues

Abstract: Arsenic (As), copper (Cu), nickel (Ni), zinc (Zn), manganese (Mn), lead (Pb), iron (Fe), aluminum (Al), cadmium (Cd) and chromium (Cr) accumulations were evaluated in the gills, hepatopancreas, exoskeleton, and muscles of Pontastacus leptodactylus (crayfi sh) (Eschscholtz, 1823). The highest metal accumulation was observed in the gills and hepatopancreas. It was detected a negative correlation between Cr-Pb, As-Cr in the muscle tissue. All other metals were displayed positive correlations with each other in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…While the causative agent of this newly detected disease remains unknown, we have performed a pilot analysis of the most likely potential causative agents recorded in literature: pathogens and metal bioaccumulation (Avila-Villa et al, 2012;Dragičević et al, 2021a;Kouba et al, 2010;Li et al, 2007;Tavabe et al, 2019;Vincent & Lotz, 2007;Wu et al, 2008). Hepatopancreas has a central role in detoxification (Wu et al, 2008) and multiple studies have demonstrated high metal accumulation in hepatopancreas (Fikirdeşici-Ergen, 2020;Gherardi, 2006;Xiong et al, 2020) and related histopathological changes similar or identical to those identified within this study (Li et al, 2007;Tavabe et al, 2019;Wu et al, 2008). Pilot analyses of water and sediment metal load revealed that both the Korana River and the reference (unpolluted) site in the Mrežnica River appear as generally clean watercourses with only somewhat higher concentrations of dissolved Mn and Fe in the surface water of both rivers, and additionally higher concentrations of As and Ba (4.5 times and 1.5-2.5 times, respectively) in the Korana River, when compared with pristine karstic rivers in and is also in line with other studies demonstrating differences between native and invasive alien crayfish in their metal requirements and rates of metal uptake, accumulation, detoxification and excretion (Gherardi, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…While the causative agent of this newly detected disease remains unknown, we have performed a pilot analysis of the most likely potential causative agents recorded in literature: pathogens and metal bioaccumulation (Avila-Villa et al, 2012;Dragičević et al, 2021a;Kouba et al, 2010;Li et al, 2007;Tavabe et al, 2019;Vincent & Lotz, 2007;Wu et al, 2008). Hepatopancreas has a central role in detoxification (Wu et al, 2008) and multiple studies have demonstrated high metal accumulation in hepatopancreas (Fikirdeşici-Ergen, 2020;Gherardi, 2006;Xiong et al, 2020) and related histopathological changes similar or identical to those identified within this study (Li et al, 2007;Tavabe et al, 2019;Wu et al, 2008). Pilot analyses of water and sediment metal load revealed that both the Korana River and the reference (unpolluted) site in the Mrežnica River appear as generally clean watercourses with only somewhat higher concentrations of dissolved Mn and Fe in the surface water of both rivers, and additionally higher concentrations of As and Ba (4.5 times and 1.5-2.5 times, respectively) in the Korana River, when compared with pristine karstic rivers in and is also in line with other studies demonstrating differences between native and invasive alien crayfish in their metal requirements and rates of metal uptake, accumulation, detoxification and excretion (Gherardi, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Mann-Whitney U-test was used to put forward whether there was a signi cant accumulation difference between muscle and gill tissues. Spearman Correlation Analysis, Principal Component Analysis (Varimax, with Kaiser Normalisation) and Cluster Analysis (Ward's method, Euclidean distance intervals and Z-score correction) were preferred to determine the metal(loid)-metal(loid) interaction (SPSS v20) (Fikirdeşici-Ergen, 2020;Tunca et al, 2013).…”
Section: Discussionmentioning
confidence: 99%